Prevalence of pathogenic Escherichia coli virulence genes in raw and domestically treated waters in Dhaka city: An overlooked health hazard analysis - Shumona, Fatema Tuj Johora; Qasem, Humaira; Monami, Humaira Tasnim; Noor, Fariha Ferdousi (Brac University, 2021)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Microbiology, 2020.